Usability testing on online transportation applications to measure user satisfaction in Padang City - Nadilla Rahma Sari; Maizul Rahmizal (Universitas Negeri Padang, 2021)
The online transportation application industry in Indonesia is experiencing very rapid growth today with the circulation of several online transportation application companies such as Grab, Gojek, and Maxim. Every online transportation application is competing to provide the best service in order to reach a large target market in Indonesia, including in the city of Padang. However, there are still many deficiencies felt by the community as users who play a very important role in the development of online transportation applications for application users in the city of Padang. This study aims to determine the level of ease, efficiency, easy to remember, error, and satisfaction as well as to find out the differences in usability testing in each online transportation application Grab, Gojek, and Maxim. The sample was determined by using cluster sampling technique with a total of 96 users. The data were collected through distributing questionnaires and then analyzed statistically descriptive and Independent-Sample T-Test with the SPSS program. The results of data analysis show that the Grab application has a good level of ease, efficiency, and easy to remember with very low errors resulting in good user satisfaction. Whereas the Gojek application has a good level of ease, efficiency, easy to remember with low errors, resulting in excellent user satisfaction. Meanwhile, the Maxim application has a sufficient level of convenience, efficiency, and easy to remember with sufficient error rate to generate sufficient user satisfaction. There is no significant difference in usability testing in the Grab application with Gojek and Grab with Maxim, but there is a significant difference in usability testing in the Gojek and Maxim applications to measure the level of user satisfaction in Padang City.